IMPLEMENTASI PENDIDIKAN KARAKTER DI UNIT PELAKSANA TEKNIS (UPT) PANTI SOSIAL PENGASUH ANAK DINAS SOSIAL PROVINSI RIAU - Putri, Rahmadini; Maemunaty, Titi; Jas, Jaspar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The formulation of the problem in this study is "how to implement character education in the Technical Implementation Unit (UPT) of the Social Care Institution of Children's Social Services in Riau Province. In accordance with the problem formulation the purpose of this study is to find out the implementation of character education in the Technical Implementation Unit (UPT) Childcare Social Institution of Riau Provincial Social Service The type of research is descriptive naturalistic with a qualitative approach that aims to find out the implementation of character education in the Technical Implementation Unit (UPT) of the Social Service Childcare Center of Riau Provincial Social Service Data collection techniques used are observation, interviews and documentation, while data analysis techniques used are data reduction, data display and data verification, as well as data validity techniques using crebility tests, transferability testing, dependability testing and confirmability testing. sound and data ventilation. This study consists of one variable implementation of character education with the indicators of this study are first (1) input, (2) instrumental input. The second implementation is in the form of (1) character education process. The three evaluations are (1) Output (2) Outcome. The subjects of this study were 5 people consisting of 2 core informants, 2 control informants and 1 observer informant. The results of the study were based on indicators, sub-indicators, dimensions on the Implementation of Character Education in the Technical Implementation Unit (UPT) Social Care Institution of the Children's Social Service Office of the Riau Province. Based on the data, the researcher made interview guidelines for 48 question items divided into 3indicator developed into 5 sub indicators and 16 dimensions namely planning, implementation and evaluation.Keywords: Implementation, Character Education